1999
DOI: 10.1007/s004280050316
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-induced alterations of matrix network in the duodenal mucosa of chronic alcohol abusers

Abstract: Excessive consumption of alcoholic beverages may be associated with gastrointestinal symptoms, including dyspepsia and diarrhoea. It is not clear whether or not chronic alcohol ingestion damages the mucosa of the small intestine. We investigated the effect of chronic alcohol abuse on the duodenal mucosa, and particularly on its extracellular matrix (ECM) network. Duodenal biopsy specimens were obtained during upper gastrointestinal endoscopy from 50 chronic alcoholics without cirrhosis and 10 healthy subjects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
(42 reference statements)
2
11
0
Order By: Relevance
“…Prenatal ethanol exposure increases the expression of COLIA1 in the fetal lung and the deposition of collagen fibers types I and III, which constitute ϳ90% of the collagens within the lung (10). These findings are similar to studies in adults that have shown that alcohol consumption results in increased procollagen type I expression in the liver, duodenum, and pancreas, resulting in fibrosis in these organs (11,12,46). An increase in collagen deposition in the lung is also associated with pulmonary fibrosis, which reduces lung distensibility, which in turn decreases forced expiratory volume and forced vital capacity (10).…”
Section: Discussionsupporting
confidence: 89%
“…Prenatal ethanol exposure increases the expression of COLIA1 in the fetal lung and the deposition of collagen fibers types I and III, which constitute ϳ90% of the collagens within the lung (10). These findings are similar to studies in adults that have shown that alcohol consumption results in increased procollagen type I expression in the liver, duodenum, and pancreas, resulting in fibrosis in these organs (11,12,46). An increase in collagen deposition in the lung is also associated with pulmonary fibrosis, which reduces lung distensibility, which in turn decreases forced expiratory volume and forced vital capacity (10).…”
Section: Discussionsupporting
confidence: 89%
“…Hydroxyproline, used as an index for total collagen content, was significantly reduced at day 7 postwounding in wounds from ethanol-treated animals compared with saline controls (5.94 Ϯ 1.56 vs. 9.43 Ϯ 0.56 g/mg wet wt). These results are consistent with previous in vitro observations in which ethanol exposure inhibited collagen synthesis by fibroblasts and increased levels of matrix-degrading proteins (4,21,34). Although these data do not reveal the mechanism, it is evident that acute ethanol exposure significantly impairs the regeneration of the dermal extracellular matrix.…”
Section: Acute Ethanol Exposure Delays Wound Reepithelializationsupporting
confidence: 92%
“…Ethanol is predominantly oxidized by ADH into acetaldehyde, which is further metabolized into acetate. Acetaldehyde is believed to induce numerous cellular alterations via increases in ROS, RNA and protein stability, and receptor levels (1,9,16,28,41). In vivo experiments using t-butanol, a tertiary long-chain alcohol known to increase membrane fluidity, did not induce changes in vascular density nor hydroxyproline content, suggesting that increasing membrane fluidity in and of itself would not inhibit wound angiogenesis.…”
Section: Discussionmentioning
confidence: 99%